PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN INTELEKTUAL TERHADAP KINERJA KARYAWAN PADA PT. BANK MANDIRI TASPEN KANTOR CABANG MELATI DENPASAR - Luh Kadek Budi Martini (Majalah Ilmiah Widyacakra, 2020)
AbstractThis Study aims to analyse the influence of emotional intelligence and intellectualintelligence to the performance of employees at PT. Bank Mandiri Taspen Kantor CabangMelati Denpasar. In this research sample is determined by the method probability sampling(simple random sampling),so by using the formula Slovin the number of samples of researchis as much as 75 people employees. The technical analysis of data used is Statistical Packagefor Social Science (SPSS). The data collection techniques used are interviews,documentation, observations, and questionnaires. Teknik analysis used is a double linearregression analysis, multiple correlation and analysis of determinations. The results showedthat the F test results in the obtained Fcount 66,192 with a significant value of 0.000 < 0.05.This means that the variable of emotional intelligence and intellectual intelligence issimultaneously significant to the employee's performance at PT. Bank Mandiri TaspenKantor Cabang Melati Denpasar. The T-Test obtained the Emotional Intelligence T-hitung1from 5,979 with a value of 0.000 <α (0.05) and an intellectual intelligence of 5,054 with asignificant value of 0.000 < α (0.05), which means variable variables of Emotionalintelligence and intellect positively and significantly affect the employee's performance at PT.Bank Mandiri Taspen Kantor Cabang Melati Denpasar.